Narrators That Alzahabi Decribed them (Pedestrians) - Alkhozaie, Faraah Abdullah (Journal of Islamic Sciences, 2019)
One of the God’s blessing for this nation that he granted a great scholars that exerted efforts in keeping Sunnah, they spoke in narrators, searched in their conditions, explained their ranks of wound and modification, one of those who interested in that was, Imam "Alzahabi", Which the research aims to determine narrators Who described them, (Pedestrians), and the statement of his intention, and the most predominant of these narrators. the researcher used the inductive and deductive approach. The most prominent findings: 1- The description of Alzahabi (Pedestrians) ) mostly is the acceptance of the narrator, 2- (Pedestrians) often documenting the narrator, The number of narrators studied (42), 3- Imams differ in the intended wound and modification, the most prominent recommendations is the Statement of the meaning of pedestrians by scholars, and know their destination so with all narrators who were described so that.